Raman Sensing and Its Multimodal Combination with Optoacoustics and OCT for Applications in the Life Sciences - Merve Wollweber; Bernhard Roth (Sensors, 2019)
Currently, many optical modalities are being investigated, applied, and further developed for non-invasive analysis and sensing in the life sciences. To befit the complexity of the study objects and questions in this field, the combination of two or more modalities is attempted. We review our work on multimodal sensing concepts for applications ranging from non-invasive quantification of biomolecules in the living organism to supporting medical diagnosis showing the combined capabilities of Raman spectroscopy, optical coherence tomography, and optoacoustics.